2020
DOI: 10.1377/hlthaff.2020.00426
|View full text |Cite
|
Sign up to set email alerts
|

The Potential Health Care Costs And Resource Use Associated With COVID-19 In The United States

Abstract: With the coronavirus disease 2019 pandemic, one of the major concerns is the burden COVID-19 will impose on the United States (U.S.) health care system. We developed a Monte Carlo simulation model representing the U.S. population and what can happen to each person who gets infected with severe acute respiratory syndrome coronavirus 2 (SARS-CoV2). We estimate resource use and direct medical costs per infection and at the national level, with various "attack rates" (infection rates) to understand the potential … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

13
279
4
9

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 330 publications
(305 citation statements)
references
References 25 publications
13
279
4
9
Order By: Relevance
“…The average direct medical costs for these patients were estimated to be $ 3,755 per person. Based on a recent study in the United States conducted by Bartsch et al the average direct medical costs per person were estimated $3,045 throughout the period of the infection (15). In this regard, the results of these two studies are comparable.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…The average direct medical costs for these patients were estimated to be $ 3,755 per person. Based on a recent study in the United States conducted by Bartsch et al the average direct medical costs per person were estimated $3,045 throughout the period of the infection (15). In this regard, the results of these two studies are comparable.…”
Section: Discussionmentioning
confidence: 95%
“…From an economic perspective, the spread of COVID-19, the ever-increasing number of patients, and the complications of the disease have imposed signi cant direct medical and indirect costs on patients, the health system and the government (12). As far as the economic burden of direct medical costs is concerned, although the costs vary with the number of the infected people, the severity of the disease, mean length of stay in the hospital, mean length of stay in the ICU, and other factors (13,14), international studies showed that medical costs of the patients with COVID-19 were signi cantly higher than those of other infectious diseases due to the higher probability of hospitalization and mortality (15). This is true about the need for COVID-19 patients for special care services and the related costs (16)(17)(18).…”
Section: Introductionmentioning
confidence: 99%
“…The average direct medical costs for these patients were estimated to be $ 3,755 per person. Based on a recent study in the United States conducted by Bartsch et al, the average direct medical costs per person were estimated $3,045 throughout the infection (15). In this regard, the results of these two studies are comparable.…”
Section: -Discussionmentioning
confidence: 96%
“…From an economic perspective, the spread of COVID-19, the ever-increasing number of patients, and the complications of the disease have imposed high direct medical and indirect costs on patients, the health system and the government (12). As far as the economic burden of direct medical costs is concerned, although the costs vary with the number of the infected people, the severity of the disease, mean length of stay in the hospital, mean length of stay in the ICU, and other factors (13,14), international studies showed that medical costs of the patients with COVID-19 were signi cantly higher than those of other infectious diseases due to the higher probability of hospitalization and mortality (15). These circumstances are also right about the need for COVID-19 patients for special care services and the related costs (16)(17)(18).…”
mentioning
confidence: 99%
“…Ventilator shortages occur in resource-rich countries as well. Previous disasters and current projections suggest that hospitals may be operating at 120-160% capacity in the face of a pandemic or national disaster 6 . Projections suggest that if 20% of the United States population is infected with the virus, there will be signi cant de ciencies in intensive care unit beds and mechanical ventilators 6,7 .…”
Section: Introductionmentioning
confidence: 99%